2002
DOI: 10.1016/s1047-8477(02)00040-0
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural properties of ciliary zonule microfibrils

Abstract: Conventional electron microscopy and rotary shadowing techniques have provided conflicting interpretations of microfibril ultrastructure. To address this issue, we have used quick-freeze deep-etch (QFDE) microscopy to obtain 3-dimensional surface views of microfibrils that have not been fixed, dehydrated, or stained with heavy metals. By this approach, microfibrils appear as tightly packed rows of bead-like subunits that do not display the interbead filamentous links seen by other methods. At regular 50-nm int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Changes in the lateral spacing also gave an insight into the organization of fibrillin-associated molecules such as MAGP-1, which in a native state may contribute to the lateral connections between microfibrils. 28,29 Previous studies on the mechanical testing of mammalian zonular filaments indicated that the application of relatively low strains produces only minor changes in the fundamental axial periodicity of the microfibrils and that this process is fully reversible. 26,30 Tissue extension of up to 50% revealed no apparent difference in the local threedimensional organization within the microfibrils, as observed from the diffraction pattern, and rearrangements were restricted to the realignment of microfibril bundles within the tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the lateral spacing also gave an insight into the organization of fibrillin-associated molecules such as MAGP-1, which in a native state may contribute to the lateral connections between microfibrils. 28,29 Previous studies on the mechanical testing of mammalian zonular filaments indicated that the application of relatively low strains produces only minor changes in the fundamental axial periodicity of the microfibrils and that this process is fully reversible. 26,30 Tissue extension of up to 50% revealed no apparent difference in the local threedimensional organization within the microfibrils, as observed from the diffraction pattern, and rearrangements were restricted to the realignment of microfibril bundles within the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…28 A study using quick-freeze deep-etch microscopy revealed a realistic view of the microfibril ultrastructure and showed small lateral filaments connecting microfibrils at regular intervals. 29 These filaments were suggested to be aggregates of MAGP-1, which play an important role in the lateral organization of microfibrils.…”
Section: Discussionmentioning
confidence: 99%
“…9 The structure of the fibrillin microfibril is of a 'beads on a string' of 10-15 nm diameter with beads 50 nm apart. 10 The bead-like structures are mostly encoded for by exon 24 of FBN1. 11 Mutations in this exon lead to severe Marfan syndrome (MFS).…”
Section: Anatomymentioning
confidence: 99%
“…The most important associated glycoprotein is MAGP-1, which probably has a role in cross linking the microfibrils. 10 …”
Section: Anatomymentioning
confidence: 99%
“…1 Recently the imaging of microfibrils in situ by the quick-freeze deep-etch (QFDE) technique revealed a different microfibril morphology. 32 Differences in microfibril morphology of extracted samples were suggested to be due to the loss of microfibrillar proteins that are associated with the fibrillin scaffold or structural changes induced by non-specific proteolysis of microfibrils. Therefore, to determine whether the fibrillin scaffold is affected by the extraction procedure, a number of different conditions have been used in this study.…”
Section: Introductionmentioning
confidence: 99%